Study on the bonding performance between reactive powder concrete and steel bar. Issue 1 (1st November 2022) - Lin, Ruizong; Yu, Xinmin; Qin, Chengcheng; Ju, Yanzhong
Abstract : The performance of reactive powder concrete (RPC) is much higher than that of ordinary concrete, and the engineering application is gradually increasing. The bond failure process and bond slip between RPC and reinforcement will show new characteristics. It is necessary to study the bond behavior between RPC and steel bar. The direct drawing test was carried out on the 36 bonding specimens in order to study the bond performance between steel bar and reactive powder concrete. The research shows that the cohesive force consists of three parts: the mechanical bite force produced by the mechanical occlusion between the reinforcing rib and the RPC; The cementing force produced by chemical reaction between RPC component and surface material of reinforcement; Friction between reinforcement and surrounding RPC. The application of ultrahigh strength and various cementitious materials make the Bonding strength between rebar and RPC significantly higher than that of normal concrete. This study can provide reference for the reinforcement anchorage design of RPC structure.